Sumber Pendapatan Negara Menurut Al-Mawardi: Analisis Konseptual dan Relevansinya dalam Sistem Ekonomi Syariah Modern - Sobarna, Nanang; Janwari, Yadi; Jubaedah, Dedah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Fiscal policy in managing state finances is the focus of Al-Mawardi's thinking in contributing his thoughts to Islamic economics. One of Fiscal policy in state finances talks about sources of state income. The aim of this research is to determine the sources of state income according to Al-Mawardi and their relevance in the modern sharia economic system. This research uses a descriptive qualitative approach, through a literature study type of research, with data analysis carried out to describe the problems studied in a clear, objective, critical and analytical manner regarding the sources of state income according to Al-Mawardi and their relevance in the modern sharia economic system. Al-Mawardi emphasized the importance of financial institutions, such as Baitul Maal, in managing state revenues, where each allocation must meet community needs proportionally. The concept of sources of state income in Al-Mawardi's perspective is not only relevant for the historical context, but also has significant applications in the modern sharia economic system which focuses on social justice and community welfare.